2017
DOI: 10.1002/admi.201700064
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Optical Properties, Electronic Structure, and Photocatalytic Activity in Nanostructured Tungsten Oxide

Abstract: cause a negative effect on the photocatalytic activity by acting as charge-recombination centers. [9] Therefore, controlling the level of V O plays an important role in defect engineering. The amount of V O in tungsten oxide was recently reported to be controlled through air-annealing at various temperatures (300-600 °C) and times (0.5-8 h), giving improvements in photocatalytic activity and electrochemical performance. [11] Recently, we have investigated the growth and properties of chemical vapor deposited (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…By contrast, the plain WO 3 nanorods showed an absorption edge higher than expected for a WO 3 film, which can be explained in terms of the synthesis method employed. It has been recently found by Ling et al that aerosol‐assisted CVD can be used to deposit WO 3 nanorods containing oxygen vacancies, which induce a quantum confinement effect. The existence of oxygen vacancies was inferred from the presence of a small amount of reduced tungsten species (W 5+/4+ ) in the as‐deposited WO 3 film, as observed by XPS analysis (Figure B) and the requirement for charge neutrality.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the plain WO 3 nanorods showed an absorption edge higher than expected for a WO 3 film, which can be explained in terms of the synthesis method employed. It has been recently found by Ling et al that aerosol‐assisted CVD can be used to deposit WO 3 nanorods containing oxygen vacancies, which induce a quantum confinement effect. The existence of oxygen vacancies was inferred from the presence of a small amount of reduced tungsten species (W 5+/4+ ) in the as‐deposited WO 3 film, as observed by XPS analysis (Figure B) and the requirement for charge neutrality.…”
Section: Resultsmentioning
confidence: 99%
“…7 To overcome this restraint, oxygen vacancies can be introduced into metal oxide lattices to extend the light absorption of these systems into the visible range. Numerous studies have explored this strategy and showed improved light absorption as well as enhanced photocatalytic activities for oxygen-decient TiO 2 [8][9][10][11][12][13][14][15] and other metal oxides such as WO 3 , [16][17][18] ZnO, 7,19,20 and SnO 2 . 21 However, enhanced performance is typically only found in the case of moderate oxygen deciency, whereas highly oxygen-decient metal oxides with strong coloration counter-intuitively exhibit signicantly lower photocatalytic activity than their stoichiometric analogues.…”
Section: Introductionmentioning
confidence: 99%
“…3f in blue colour) suggested that the presence of oxygen deficient in surface. 44 The metal NPs were deposited on the as-synthesized WO 3 NR array, with the size controlled by the deposition time (0.5 to 36 min) during AACVD. The obtained metal NPs/WO 3 NRs hybrid nanostructure thin films are denoted as M/WO 3 ('t' minutes), where 't' is the deposition time for the metal precursor during AACVD.…”
Section: Resultsmentioning
confidence: 99%
“…The sample Au/WO 3 (1 min, with particle mean size 3.0 nm) and sample Pt/WO 3 (10 min, 3.0 nm) showed enhanced activity for photocatalytic degradation of SA with FQE = 11.0 × 10 −5 and 11.3 × 10 −5 respectively compared to an undecorated WO 3 NR array thin film (deposition time of 5 minutes, FQE = 8.7 × 10 −5 which was the best photocatalytic activity for WO 3 NRs array thin films according to our previous study). 44 Whereas, when the WO 3 NR array was functionalised by Pd and Ru NPs (sample Pd/WO 3 (5 min, 1.9 nm) and Ru/WO 3 (36 min, 2.8 nm)) a lower activity for photocatalytic degradation of SA was observed. After annealing, the sample PdO/WO 3 (5 min, 5.6 nm) had the highest activity for photocatalytic degradation of SA with FQE = 13.2 × 10 −5 , though RuO 2 /WO 3 (36 min, 5.1 nm) still showed lower activity (FQE = 6.0 × 10 −5 ).…”
Section: Nanoscale Papermentioning
confidence: 97%
See 1 more Smart Citation